2015
DOI: 10.1016/j.learninstruc.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Math achievement, stereotypes, and math self-concepts among elementary-school students in Singapore

Abstract: a b s t r a c tSingaporean elementary-school students (N ¼ 299) completed Child Implicit Association Tests (Child IAT) as well as explicit measures of gender identity, mathegender stereotypes, and math self-concepts. Students also completed a standardized math achievement test. Three new findings emerged. First, implicit, but not explicit, math self-concepts (math ¼ me) were positively related to math achievement on a standardized test. Second, as expected, stronger mathegender stereotypes (math ¼ boys) signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(101 citation statements)
references
References 70 publications
5
91
2
3
Order By: Relevance
“…First, our behavioral data showed that only the main effect of aging stereotype condition was marginally significant. This result indicates that behavioral data do not support the notion that priming aging ST could activate the working self-concept—a finding which is inconsistent with previous studies (Schmader et al, 2014; Cvencek et al, 2015). One possible reason is that behavioral data may not be sensitive enough.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…First, our behavioral data showed that only the main effect of aging stereotype condition was marginally significant. This result indicates that behavioral data do not support the notion that priming aging ST could activate the working self-concept—a finding which is inconsistent with previous studies (Schmader et al, 2014; Cvencek et al, 2015). One possible reason is that behavioral data may not be sensitive enough.…”
Section: Discussioncontrasting
confidence: 92%
“…Two such notable omissions, which have been increasingly investigated in the context of other types of STs, concern the effects of the aging ST on working self-concept and the neural mechanisms underlying these effects (e.g., Schmader et al, 2014; Cvencek et al, 2015). Our article aims to address this gap in the current existing literature.…”
Section: Introductionmentioning
confidence: 99%
“…Self-concepts in turn, are consequently to the social-cognitive theory, strongly related to an individual's achievement (Denissen, Zarrett, & Eccles, 2007). A wide range of studies have not only corroborated the BFLPE, but also found this positive relation of self-concept with achievement in mathematics and science (e.g., Antunes & Fontaine, 2013;Cvencek, Kapur, & Meltzoff, 2015;Jansen, Schroeders, & Lüdtke, 2014;Lee & Kung, 2018;Ma & Kishor, 1997;Sahranavard, Hassan, Elias, & Abdullah, 2012;Wang, Oliver, & Staver, 2008). Guided by this theoretical framework, Höffler et al (2017) and Chang and Lin (2017) found that also within a science Olympiad reference framework, participants' academic self-concept was significantly correlated with their academic achievement.…”
Section: Theories Used To Explain Participation and Achievement In mentioning
confidence: 87%
“…In his study Jones (1991) suggested that masculine associations with physics and feminine associations with biology explain the uneven distribution of male and female participants. These associations related to the fields of mathematics and science are known as gender-mathematics and gender-science stereotypes, which are generally endorsed beliefs that males are naturally more talented and interested in mathematics and science than females (Cvencek et al, 2011;Cvencek et al, 2015;Farrell, Cochrane, & McHugh, 2015;Farrell & McHugh, 2017;Hyde & Linn, 2006;Liu, Hu, Jiannong, & Adey, 2010;Nosek et al, 2007;Nosek et al, 2009;Smyth & Nosek, 2015;Spencer, Steele, & Quinn, 1999;Steffens & Jelenec, 2011). Not only do gender-mathematics and gender-science stereotypes imply that males are more talented at mathematics and science, they also suggest that these fields are generally considered to be masculine (Kelly, 1985).…”
Section: Gender-mathematics and Gender-science Stereotypesmentioning
confidence: 99%
See 1 more Smart Citation